Tăng cường trích dẫn và ảnh hưởng học thuật của Đại học Quốc gia Hà Nội thông qua trắc lượng thư mục VNU-LIC - Nguyễn, Huy Chương (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Statistics, analysis of citations through typical indicators such as Impact Factor (IF), H-Index to evaluate and rank individuals and scientific organizations, effectively support users in believing in search and exploit information. For many years, the Information and Library Center, Vietnam National University (VNU-LIC) has implemented this activity quite effectively. Hopefully, in the coming time, VNU-LIC will continue to promote the application of directory survey to increase the utility for private users and contribute to improving the ranking of Vietnam National University, Hanoi.